Measurement of substrate oxidation during exercise by means of gas exchange measurements - Jeukendrup, A. E.; Wallis, G. A. (International Journal of Sports Medicine, 2005)
Measures of substrate oxidation have traditionally been calculated from indirect calorimetry measurements using stoichiometric equations. Although this has proven to be a solid technique and it has become one of the standard techniques to measure whole body substrate metabolism, there are also several limitations that have to be considered. When indirect calorimetry is used during exercise most of the assumptions on which the method is based hold true although changes in the size of the bicarbonate pool at higher exercise intensities may invalidate the calculations of carbohydrate and fat oxidation. Most of the existing equations are based on stoichiometric equations of glucose oxidation and the oxidation of a triacylglycerol that is representative of human adipose tissue. However, in many exercise conditions, glycogen and not glucose is the predominant carbohydrate substrate. Therefore we propose slightly modified equations for the calculation of carbohydrate and fat oxidation for use during low to high intensity exercise. Studies that investigated fat oxidation over a wide range of intensities and that determined the exercise intensity at which fat oxidation is maximal have provided useful insights in the variation in fat oxidation between individuals and in the factors that affect fat oxidation. Fat oxidation during exercise can be influenced by exercise intensity and duration, diet, exercise training, exercise mode and gender. Although a number of important factors regulating fat oxidation have been identified, it is apparent that a considerable degree of inter-subject variability in substrate utilization persists and cannot be explained by the aforementioned factors. Future research should investigate the causes of the large inter-individual differences in fat metabolism between individuals and their links with various disease states.